Symmetrical Political Communication Strategies and Hybrid Leadership in Jayapura City - Yakobus Richard Murafer; Terianus Luther Safkaur; Eduard Metusala Yohanis Kocu; Jackson Yumame (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study addresses the structural challenge of public distrust in the Special Autonomy region of Papua. The main focus of this study is to analyse the communication strategy of the Mayor of Jayapura in restoring this trust through the innovative interactive dialogue programme ‘Torang Tanya, Wali Kota Jawab’. Using a descriptive qualitative case study design, this study evaluates the one-way information model to an egalitarian, dialogue-based model. The research analysis framework focuses on three main theoretical pillars, namely the Two-Way Symmetrical Communication Theory, Dramaturgi Politik to analyse the integration of the leader's performance on the front stage with the technical readiness of the OPD on the back stage, The OECD's Public Trust Variable, which encompasses the dimensions of responsiveness, competence, transparency, and integrity. The research findings the programme successfully implemented Hybrid Governance, combining the efficiency of modern bureaucracy with local Papuan wisdom. The study also identified the 'paradox of bureaucratic success', where a reduction in the quantity of citizen participation.